SIDELINE MANAGEMENT OF ACUTE DISLOCATION OF THE GLENOHUMERAL JOINT‐ A UNIQUE APPROACH TO ATHLETE SELF‐REDUCTION - Smith, Danny (Sports Physical Therapy Section, 2013)
The acute anterior dislocation of the glenohumeral joint (GHJ) poses a challenge to sports medicine providers at all levels and in all settings. This macrotraumatic injury occurs in athletes who participate in a wide variety of sports, most typically as a result of contact or collision mechanisms. Quick and effective relocation of the GHJ is an important skill for on the sideline or on the field management of this type of dislocation when appropriate and allowable by facility protocol. This clinical suggestion describes one possible technique for athlete self‐reduction that may be appropriate in some circumstances. This is in contrast to forcible reduction by the health professional, which is outside of the scope of this clinical commentary. LEVEL OF EVIDENCE: 5